Gas chromatographic retention data of wax esters - Stránský, Karel; Zarevúcka, Marie; Valterová, Irena; Wimmer, Zdenek (Journal of chromatography. A, 2006)
Higher wax esters within the range of C24 to C44 (205 standards) were analyzed by means of gas chromatography and Kováts indexes (I) and reduced Kováts indexes (RKI) were calculated. The dependences of these retention data on number of carbon atoms and on number and position of double bonds in acid and in alcohol moieties of esters were plotted.
Keywords: Esters; Waxes; Fatty Acids; vosky; estery; mastné kyseliny; Chromatography, Gas; chromatografie plynová